2021
DOI: 10.3390/ijerph18073433
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Neuromuscular Electrical Stimulation and Insulin Therapy on Glycated Hemoglobin Concentrations, Lipid Profiles and Hemodynamic Parameters in Patients with Type-2-Diabetes and Hemiplegia Related to Ischemic Stroke: A Pilot Study

Abstract: Type-2-diabetes mellitus (T2DM) is a global problem of medical, social and economic consequences. Physical activity is a vital therapy in patients with T2DM, but some of them cannot exercise for various reasons. The purpose of our pilot study was to determine whether a combination of neuromuscular electrostimulation (NMES) and insulin therapy could improve the management of T2DM patients with hemiplegia caused by an ischemic stroke. Fifteen immobile patients with T2DM on insulin therapy were enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Similar to our study, Khost et al [27] showed that foot massage increased the oxygen saturation of arterial blood in patients with stroke. Rubinowicz-Zasada et al [28] also showed that electrical neuromuscular stimulation in combination with diabetes treatments in diabetic patients with stroke can be effective in lowering blood pressure in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Khost et al [27] showed that foot massage increased the oxygen saturation of arterial blood in patients with stroke. Rubinowicz-Zasada et al [28] also showed that electrical neuromuscular stimulation in combination with diabetes treatments in diabetic patients with stroke can be effective in lowering blood pressure in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the HbA1c level reduced following 8 weeks of NMES, but not significantly. However, the results of previous studies on the effect of NMES on HbA1c levels in patients with type-2 diabetes were contradictory [ 9 , 15 , 23 , 24 ]. Louis Crow et al showed that 8 weeks of electrical stimulation reduced HbA1c levels significantly in men with type-2 diabetes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the contradictory result was reported by Oonagh M. Giggins et al, that eight-week electrical stimulation did not lead to significant changes in HbA1c levels in patients with type-2 diabetes [ 9 ]. In another study, the findings indicated that 12 weeks of NMES in patients with type-2 diabetes and cerebral palsy reduced the levels of HbA1c, total cholesterol and LDL significantly [ 24 ]. These conflicting results may be due to the differences in the electrical stimulation parameters applied and the duration of the intervention or the sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients with T2DM and hemiplegia caused by a stroke, or motor system disorders, cannot exercise. The results of clinical studies indicate that physical exercise could be replaced in such cases by Neuromuscular Electrical Stimulation (NMES) [5]. In our pilot study [5] was to determine whether a combination of Neuromuscular Electro Stimulation (NMES) and insulin therapy could improve the management of T2DM patients with hemiplegia caused by an ischemic stroke.…”
Section: Opinionmentioning
confidence: 99%
“…The results of clinical studies indicate that physical exercise could be replaced in such cases by Neuromuscular Electrical Stimulation (NMES) [5]. In our pilot study [5] was to determine whether a combination of Neuromuscular Electro Stimulation (NMES) and insulin therapy could improve the management of T2DM patients with hemiplegia caused by an ischemic stroke. Fifteen patients with T2DM on insulin therapy and post-stroke hemiplegia were enrolled in the study.…”
Section: Opinionmentioning
confidence: 99%